Políticas públicas e história da educação - Oliveira, Anderson Augusto do N. (RCMOS - Revista Científica Multidisciplinar O Saber, 2024)
This research presents a study on the employability of the world’s “marijuana” and “cannabis” in selected articles from the G1 news portal in 2022. The corpus of this research consists of 31 articles extracted from the G1 news portal, using the following keywords for search: “marijuana G1” and “cannabis G1”. The investigation sought to understand the context behind the use of the term “marijuana” and the term “cannabis” in selected subjects. The study brings contributions to journalism through the observation of journalistic news, pointing out its infl uences in the construction of social representation related to the herb in Brazilian society.